Managing knowledge workers' commitment in small construction professional firms - Mohyin, Nur Affah; Dainty, A. R. J.; Carrillo, P. M. (2009)
Construction professional services (CPS) rely heavily on knowledge workers as their main resources in delivering their services. One of the main concerns in managing these workers is the development and maintenance of organisational commitment. Smaller firms, with more informal human resource management systems and practices are more likely to face challenges in managing their knowledge workers’ commitment. Arguably, the intrinsic characteristics of the construction industry mean that this effort of managing knowledge workers’ commitment will require an appropriate management framework for its successful implementation. This research seeks to develop a framework for informing the management of knowledge workers in a way that fosters organisational commitment in small CPS firms. Interviews with the employers of small CPS firms were conducted to explore some of the important issues such as the strategies and challenges associated with effectively managing knowledge workers’ organisational commitment. The findings reveal that employers associate commitment with loyalty and high quality work. Many strategies are used to influence commitment such as performance-based compensation, close working relationship, training, employee involvement in decision making and two-way communication. Meanwhile, the provision of job security and career advancement were seen as the biggest challenges in managing knowledge workers’ commitment. Finally, we conclude with limitations and implications of the findings that provide directions for future research.